1987
DOI: 10.1093/geronj/42.6.620
|View full text |Cite
|
Sign up to set email alerts
|

Sleep-Disordered Breathing in Healthy Aged Persons: Possible Daytime Sequelae

Abstract: We assessed the overnight sleep and breathing as well as daytime medical, sleep, and psychological status of a group of 34 healthy older persons. Analyses indicated that sleep-disordered breathing (SDB) was not related to any aspects of daytime functioning as measured in this study and that persons with an apnea + hypopnea index (AHI) greater than or equal to 5 (M AHI = 14.6) were not significantly impaired relative to those with lower levels of SDB (M AHI = 1.0) on any aspect of daytime performance. We conclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…4,16 In addition, research examining daytime sleepiness in relation to performance or vigilance in healthy elderly has failed to show a significant correlation, 17 and some, but not all, studies comparing severity of specific sleep disorders and traditional measures of EDS have also shown weak or no association. [18][19][20] There have been relatively few studies that have examined the functional outcomes of excessive daytime sleepiness in older adults. These studies have generally examined the effects of EDS in specific domains such as falls, 11 cognitive function, 4 and cardiovascular events.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4,16 In addition, research examining daytime sleepiness in relation to performance or vigilance in healthy elderly has failed to show a significant correlation, 17 and some, but not all, studies comparing severity of specific sleep disorders and traditional measures of EDS have also shown weak or no association. [18][19][20] There have been relatively few studies that have examined the functional outcomes of excessive daytime sleepiness in older adults. These studies have generally examined the effects of EDS in specific domains such as falls, 11 cognitive function, 4 and cardiovascular events.…”
Section: Resultsmentioning
confidence: 99%
“…It is often viewed as a nonspecific complaint and closely related to depression 4,16 . In addition, research examining daytime sleepiness in relation to performance or vigilance in healthy elderly has failed to show a significant correlation, 17 and some, but not all, studies comparing severity of specific sleep disorders and traditional measures of EDS have also shown weak or no association 18–20 …”
mentioning
confidence: 99%
“…The effect of average oxygen saturation has, somewhat surprisingly, not been reported in any of the eight identified previous community-based studies or studies of mild OSA [1217]. Studies of cognitive function in clinical samples of moderate to severe OSA have reported a similar level of average oxygen saturation as our study [7, 39, 40], and a recent study also found that average oxygen saturation was an independent predictor of cognitive decline in middle-aged adults with moderate to severe OSA [41].…”
Section: Discussionmentioning
confidence: 98%
“…We identified seven community-based studies [1218] and two studies of mild OSA in volunteers [19, 20] that assessed cognitive function with rater-administered instruments in addition to objective sleep measures. Four studies reported associations between OSA and at least one cognitive domain [13, 14, 19, 20].…”
Section: Introductionmentioning
confidence: 99%
“…Apnoea/hypopnoea severity in the elderly does not appear to be related to daytime neuropsychological dysfunction. [83][84][85] Similarly, the relationship between sleep disordered breathing and dementia is controversial.86 Some studies find no increase in sleep disordered breathing in patients with Alzheimer's disease,87 whereas others have shown more sleep disordered breathing in patients with multi-infarct and Alzheimer's dementia. 88 Currently there is no justification to screen elderly or demented patients for sleep disordered breathing, but it is important to consider this diagnosis in any patient with associated symptoms consistent with sleep disordered breathing.…”
Section: Neurological Consequences Cerebrovascular Diseasementioning
confidence: 99%